Post-Olympic Games venue developments: a life circle view - Cheng, X.; You, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: With the ongoing development of the Olympic Games, the number of Games` venues increases generally whilst the standards of venues improve. Research indicates that the Games spur the economy of the host cities, and the construction of these substantial venues creates a significant burden for host cities[1]. The post-Games development of the Games` venues is an academic issue and it is evident that benefit should be maximized during the different periods based on the venue project`s different goals. This should occur according to the conditions of the district system where the venues are located, and within the context of life cycle. In-depth discussion of this issue has theoretical and practical significance in terms of enriching the project management theory. Such discussion may impact upon the interaction mechanism between the venue projects and the district system where the venues are located, and maintain their sustainable development. Methods This study analyzed the venues of recent Olympic Games, with reference to the project management theory, system theory, input-output analysis theory, industry cluster theory, and other relative theories, and the methods of induction and deduction. Further, this paper addresses the interaction between major venue projects and the district system where the venues were located, before, during, and after the Games, within the context of life cycle. Influencing factors of the post-Games development of the venues in the light of the interaction mechanism were analyzed. The analysis considered variables linked to investment scale, area occupied, location, sport events character, GDP, population structure, consumption levels and consumer preference, Also the development level of the relative industries before, during, and after the Games was considered. Cluster analysis was then used to assess the major factors which impact on the post-Games development of venues. The advantages and disadvantages of the various post-Games development modes of the recent Games` venues are summarized, and the post-Games development modes system for the venues are established. Results The Olympic Games venues improve the relative industries of a host district in areas including real estate, culture, sports, entertainment, and the hotel and catering industries. This occurs through enlarged industry requirement, upgrades of industry structure, and the exploration of the space of industry development, all within the context of life circle. It is these industries that provide the groundwork to maintain sustainable development of the venues. Cluster analysis reflects that GDP, consumption levels ad consumer preference, and the development level of the relative industries are the main factors that impact upon the post-Games development of the venues. There are three major development modes for the venues: single-function, multi-function, changing function. Conclusions The construction of the interaction mechanism between the major venue projects and the district system where the venues are located, within the context of life circle, improves the project management theory[2]. Further, influencing factors and development modes are prioritised in light of the interaction mechanism. These conclusions have great meaning for the host cities to select the post-Games development strategies for the venues, based on localised requirements.